Pituitary volumes of the patients with borderline personality disorder are not changed - Atmaca, Murad; Karakoc, Tevfik; Mermi, Osman; Kilic, Faruk; Gurok, M. Gurkan; Yildirim, Hanefi (Sage Publications Inc, 2015)
Although it has important relationships with psychiatric symptoms via the hypothalamic-pituitary-adrenal axis, there have been limited investigations of pituitary neuroimaging in psychiatric disorder. Moreover, there have been no studies of borderline personality disorder. In the present investigation, we examined pituitary gland volumes in patients with borderline personality disorder. Seventeen right-handed female patients with borderline personality disorder, selected among the patients who had presented to Firat University School of Medicine Department of Psychiatry outpatient and inpatient clinics, and the same number of healthy control subjects were included in the present investigation. Pituitary gland volumes were manually detected. The results demonstrated that the mean volumes of the gland of the patients with borderline personality disorder were not significantly different than those of healthy control subjects (mean volume of 0.79 cm(3) in the patient group, with a value of SD +/- 0.11 and 0.81 cm(3) in the healthy control group, with a value of SD +/- 0.23; t = -0.21; p > 0.05).
Keywords: Borderline personality disorder; pituitary gland volume; magnetic resonance imaging